Composição bioquímica de organismos planctônicos visando à aplicação em aquicultura - Rocha, Giseli Swerts (2014)
Aquaculture is an activity of great importance in food production, but fish survival in post- larval stages represents a big challenge. Artemia sp. is successfully used as live food, but is expensive and one of the alternatives to reduce costs is to use native species, such as natural zooplankton and fairy shrimp Dendrocephalus brasiliensis, phylogenetically close to A. salina. This study examined how changes in nutritional conditions affect the algae Ankistrodesmus gracilis, and the biochemical composition of D. brasiliensis, Artemia sp. and Daphnia magna. Moreover, we studied how different combinations of food affect the biochemical composition of Atlantic cod (Gadus morhua). The results showed that the availability of phosphorus and copper alter the biochemical composition of algae and affect the production of chlorophyll, growth rates and resistance to metal; D. brasiliensis showed good results in terms of the content of carbohydrates and protein, and a change in the lipid composition according to sex and stage of development of animals; cod showed better results when feed on wild zooplankton added to the cultivated and enriched organisms (rotifers and Artemia) in tanks. Based on these results, we conclude that the environment and nutrient availability in the case of microalgae, affects the biochemical composition and ability to handle contaminants. The biochemical composition of zooplankton can affect higher trophic levels, affecting both the biochemical composition. For these reasons, it is important to know the optimal cultivation conditions in order to achieve the best results in each trophic level.